Recommendations for the use of cladribine tablets for the pathogenetic treatment of patients with highly active multiple sclerosis - K. Z. Bakhtiyarova; A. N. Boyko; Ya. V. Vlasov; Z. A. Goncharova; M. V. Davydovskaya; M. N. Zakharova; N. A. Malkova; A. I. Nilov; S. A. Sivertseva; N. N. Spirin; N. A. Totolyan; F. A. Khabirov; et al. (Неврология, нейропсихиатрия, психосоматика)
Currently, special attention is paid to timely treatment for active forms of multiple sclerosis (MS), especially for highly active MS (HAMS), in which there are ≥2 exacerbations and corresponding activity signs that are detected by magnetic resonance imaging (MRI) regardless of previous therapy with MS-modifying drugs (MSMDs) or there is ≥1 exacerbation and corresponding activity signs revealed by MRI during therapy with other MSMDs. A group of expert neurologists from various clinics in Russia, who actively participate in the clinical trials of cladribine tablets in MS, presents a consensus on the practical aspects of using the tablets of cladribine registered in Russia in March 2020 for the treatment of patients with HAMS. The paper mentions the groups of patients in whom the drug, an examination before starting a therapy cycle, routes of administration, and dose, and a monitoring scheme during and after treatment cycles are indicated. This drug acts on the principle of selective immunoreconstitution and may occupy an important place in the treatment of HAMS.